Cross-cultural adaptation and validation of the 22-item sinonasal outcome test (SNOT-22) in German-speaking patients: a prospective, multicenter cohort study - Albrecht, Tobias; Beule, Achim Georg; Hildenbrand, Tanja; Gerstacker, Kathrin; Praetorius, Mark; Rudack, Claudia; Baumann, Ingo (European archives of oto-rhino-laryngology and head & neck, 2022)
Chronic rhinosinusitis (CRS) is a common condition associated with a significant reduction of the health-related quality of life. One of the most widely used assessment tools in CRS is the disease-specific, health-related questionnaire SNOT-22. The aim of this study was to translate and validate the SNOT-22 into the German language.
Online veröffentlicht 05. August 2021
Gesehen am 24.05.2023